EXECUTIVE ACADEMIC LEADERSHIP THAT AFFECTS THE QUALITY OF EDUCATION MANAGEMENT OF SCHOOL UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Thongnual, Chatupong; Dhammatikul, Akara; Chataka, Werayut (Journal of MCU Nakhondhat, 2023)
The purpose of this research were to study academic leadership. study the quality of education management and to create a forecasting equation of academic leadership that affects the quality of school education. Under the Office of Primary Educational Service Area Nakhon Si Thammarat District 1. The samples used were teachers and personnel. The samples were 306 students under the Office of Nakhon Si Thammarat Primary Educational Service Area 1. Data were analyzed using statistics: percentage, mean, standard deviation. Multiple regression analysis The research results found that 1) Academic Leadership of School Administrators under the Office of Nakhon Si Thammarat Primary Educational Service Area, Area 1 overall and each side at a high level Ranked from the average to the least, including promoting the academic atmosphere of the school. in terms of setting goals and missions of the school Educational supervision and teaching and learning, respectively. 2) The quality of educational management of educational institutions under the Office of Nakhon Si Thammarat Primary Educational Service Area, Region 1 overall and each aspect were at a high level. Ordered from average to least, including the teaching and learning process that focuses on the student is important. administrative processes and management of school administrators and student quality, respectively. 3) Academic Leadership of Educational Institution Administrators There was a positive relationship with the quality of educational management of educational institutions. under the Office of Nakhon Si Thammarat Primary Educational Service Area, Region 1 with statistical significance at the .01 level. and educational supervision able to predict the quality of educational management of educational institutions Overall, 49.30 percent can be constructed as a regression equation in terms of raw scores and in terms of standard scores, i.e. regression equations in terms of raw scores, tot=1.822+.156(X1)+.433(X4) and Regression equation in standard score form tot=.233(X1)+.578(X4)